Research Trends in Radioisotopes: A Scientometric Analysis (1993-2012) - Sagar, Anil; Kademani, B.S.; Bhanumurthy, K.; Ramamoorthy, N. (DESIDOC Journal of Library & Information Technology, 2014)
This paper attempts to highlight the publication status and growth of radioisotope research across the world and make quantitative and qualitative assessment by way of analysing various features of research output based on Web of Science database during the period 1993-2012. A total of 31488 publications were published on radioisotopes, which received 482549 citations. The average number of publications per year was 1574.40 and the average number of citations per publication was 15.32. The publications peaked in the year 2012 with 2036 publications and the highest number of citations (33316) was in 1999. The parameters studied include: year-wise growth of publications and citations, continent-wise distribution of publications and citations, country-wise distribution of publications, distribution of publications according to impact factor range, international collaboration, domain-wise distribution of publications and citations, highly productive institutes, highly cited publications and highly preferred journals for publications by scientists. doi: 10.14429/djlit.34.7833